Dual source coronary computed tomography angiography for detecting in-stent restenosis. Issue 7 (19th September 2007) - Pugliese, F; Weustink, A C; Van Mieghem, C; Alberghina, F; Otsuka, M; Meijboom, W B; van Pelt, N; Mollet, N R; Cademartiri, F; Krestin, G P; Hunink, M G M; de Feyter, P J
Abstract : Objective: To evaluate the performance of dual source CT coronary angiography (DSCT-CA) in the detection of in-stent restenosis (⩾50% luminal narrowing) in symptomatic patients referred for conventional angiography (CA). Design/patients: 100 patients (78 males, age 62 (SD 10)) with chest pain were prospectively evaluated after coronary stenting. DSCT-CA was performed before CA. Setting: Many patients undergo coronary artery stenting; availability of a non-invasive modality to detect in-stent restenosis would be desirable. Results: Average heart rate (HR) was 67 (SD 12) (range 46–106) bpm. There were 178 stented lesions. The interval between stenting and inclusion in the study was 35 (SD 41) (range 3–140) months. 39/100 (39%) patients had angiographically proven restenosis. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of DSCT-CA, calculated in all stents, were 94%, 92%, 77% and 98%, respectively. Diagnostic performance at HR <70 bpm (n = 69; mean 58 bpm) was similar to that at HR ⩾70 bpm (n = 31; mean 78 bpm); diagnostic performance in single stents (n = 95) was similar to that in overlapping stents and bifurcations (n = 83). In stents ⩾3.5 mm (n = 78), sensitivity, specificity, PPV, NPV were 100%; in 3 mm stents (n = 59), sensitivity and NPV were 100%, specificity 97%, PPV 91%; in stents ⩽2.75 mm (n = 41), sensitivity was 84%, specificity 64%, PPV 52%, NPV 90%. Nine stents ⩽2.75 mm were uninterpretable. Specificity of DSCT-CA in stents ⩾3.5 mm was significantly higher than in stents ⩽2.75 mm (OR  = 6.14; 99%CI: 1.52 to 9.79). Conclusion: DSCT-CA performs well in the detection of in-stent restenosis. Although DSCT-CA leads to frequent false positive findings in smaller stents (⩽2.75 mm), it reliably rules out in-stent restenosis irrespective of stent size.